Pengaruh Hubungan Ayah dan Anak Menurut Amsal 4:11-12 Terhadap Kesehatan Emosional Anak di Gereja JKI Anugerah Allah – Sidoarjo (International Forum of Researchers and Lecturers, 2024)
The role of a father is crucial in a family for the emotional health of Generation Z children. However, the phenomenon occurring, particularly in the JKI Anugerah Allah church in Sidoarjo, has not been adequately controlled. The aim of this paper is to provide a deeper understanding of the importance of the quality of the father-child relationship and the significance of the church's involvement in supporting it. The method used is qualitative with a case study approach. In certain cases, during Sunday School services, some children, especially boys, still appear indifferent to the activities and show little respect for the Sunday School teachers. Therefore, it is essential for the church and family to collaborate in taking appropriate actions for the emotional well-being of children in the future.